Endoscopic Mucosal Resection Performed Underwater for Nonampullary Duodenal Epithelial Tumor: Evaluation of Feasibility and Safety. (9th August 2018) - Shibukawa, Goro; Irisawa, Atsushi; Sato, Ai; Abe, Yoko; Yamabe, Akane; Arakawa, Noriyuki; Takasaki, Yusuke; Maki, Takumi; Yoshida, Yoshitsugu; Igarashi, Ryo; Yamamoto, Shogo; Ikeda, Tsunehiko; et al.
Abstract : Objectives . Recently, opportunities to encounter superficial nonampullary duodenal epithelial tumor (SNADET) have increased. EMR and ESD are performed to treat SNADET. However, the rate of perforation is higher than that of other gastrointestinal lesions, regardless of which method is used. Underwater EMR (UW-EMR) is immersion treatment of SNADET, which has low risk of perforation and can remove lesions safely and completely. In the present study, we retrospectively investigated patients in whom UW-EMR was performed to evaluate the feasibility and safety of UW-EMR for the treatment of SNADET. Methods . The primary endpoint was to evaluate the feasibility of UW-EMR for the treatment of SNADET, and secondary objective was to determine the operation's safety. Results . There were 14 participants, with a total of 16 lesions, who underwent UW-EMR between August 2015 and December 2017. Histological heteromorphism revealed that seven patients had low-grade adenoma, seven had high-grade adenoma, and two had adenocarcinoma. En bloc resection was performed in 14 lesions. In two patients, nodular lesions were observed in the scar and biopsy confirmed recurrences. There were no serious adverse events including bleeding or perforation. Conclusions . UW-EMR may be a safe and effective treatment method for SNADET, if its therapeutic indication is adequately considered.